Microbial Dynamics in Periodontal Regeneration: Understanding Microbiome Shifts and the Role of Antifouling and Bactericidal Materials: A Narrative Review - Nada Tawfig Hashim; Rasha Babiker; Sivan Padma Priya; Riham Mohammed; Nallan CSK Chaitanya; Vivek Padmanabhan; Shadi El Bahra; Muhammed Mustahsen Rahman; Bakri Gobara Gismalla (Current Issues in Molecular Biology)
Periodontal regeneration is a multifaceted therapeutic approach to restore the tooth-supporting structures lost due to periodontal diseases. This manuscript explores the intricate interactions between regenerative therapies and the oral microbiome, emphasizing the critical role of microbial balance in achieving long-term success. While guided tissue regeneration (GTR), bone grafting, and soft tissue grafting offer promising outcomes in terms of tissue regeneration, these procedures can inadvertently alter the oral microbial ecosystem, potentially leading to dysbiosis or pathogenic recolonization. Different grafting materials, including autografts, allografts, xenografts, and alloplasts, influence microbial shifts, with variations in the healing timeline and microbial stabilization. Biologics and antimicrobials, such as enamel matrix derivatives (EMD) and sub-antimicrobial dose doxycycline (SDD), play a key role in promoting microbial homeostasis by supporting tissue repair and reducing pathogenic bacteria. Emerging strategies, such as enzyme-based therapies and antifouling materials, aim to disrupt biofilm formation and enhance the effectiveness of periodontal treatments. Understanding these microbial dynamics is essential for optimizing regenerative therapies and improving patient outcomes. The future of periodontal therapy lies in the development of advanced materials and strategies that not only restore lost tissues but also stabilize the oral microbiome, ultimately leading to long-term periodontal health.